Embracing the Cascade: evidence-based medicine. (2nd September 2019) - Redpath, Adam; Bowen, Mark
Abstract : The prescribing cascade is a risk-based algorithm that is applied on a case-by-case basis when selecting medicines that are not authorised in a given clinical scenario. It allows for the use of other veterinary medicines, whether authorised in the horse or other species, the use of human medicines from the UK and veterinary medicines from the EU or the use of specials (compounded or medicines produced extemporaneously). Its application brings with it several professional obligations and responsibilities, including the need to obtain written consent. Given the potential food-producing status of the horse, equine veterinary surgeons have additional considerations compared to those working with other species (whether farm animal or companion). Medicine selection under the Cascade must be based on valid justifications for not using authorised medicines (where available) and for the selection of subsequent steps in the Cascade. These justifications should be based on clinical need and a robust evidence base. Given that the Cascade exists to improve animal welfare, cost should not normally be considered as a reason for selecting medicines in the horse.